Assessment of radioactivity levels in coal and coal ash in Kiwira coal mine using gamma-ray spectrometry - Makundi, Ismael N; Nyaki, Mungubariki M; Mohammed, Najat K (Tanzania Journal of Science, 2021)
This study aimed to assess the radioactivity levels and associated dose rates from the naturally occurring radionuclides 226Ra, 232Th and 40K in coal and coal ashes at Kiwira coal mine. The radioactivity of 40 representative coal, fly ash samples were measured using gamma spectroscopy of the Tanzania Atomic Energy Commission (TAEC) in Arusha, Tanzania. The activity concentrations of 226Ra, 232Th and 40K in coal and coal ashes from Kiwira were higher by several orders of magnitude than their worldwide average values. The calculated radium equivalent activity, the air absorbed dose rate, external hazard index and the average annual effective dose rate in fly ashes were 1335 ± 60 Bq kg-1, 610 ± 29 nGy h-1, 4 ± 0.4, 738 ± 52 µSv y-1 which were higher than the international recommended values of 370 Bq kg-1, 57 nGy h-1, and 70 µSv y-1 for fly-ashes respectively. The results provide information for the radiation protection when the coal and its by-products in the vicinity of Kiwira coal field is used. The data can be used by the authorities to design an appropriate method for handling wastes and implement intervention measures to protect the miners, the public as well as the environment.